Uji Berbagai Produk Insektisida dalam Mengendalikan Hama Ulat Api (Setothosea asigna Eecke.) pada Bibit Kelapa Sawit (Elaeis guineensis Jacq.) - Manurung, Yohana; Fauzana, Hafiz (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This Setothosea asigna is one of the main pests that attack oil palm. S. asigna pest control can be done by using insecticides cypermethrin, Bacillus thuringiensis,Beauveria bassiana and Azadirachta indica. The aim of this study was to determine the ability of various insecticide products to control S. asigna. research was carried out experimentally using a completely randomized design (CRD) consisting of 5 treatments and 4 replications, in order to obtain 20 experimental units. Each experimental unit consisted of 10 S. asigna larvae. The treatments given were various insecticide products consisting of 5 treatments, namely: no insecticide, cypermethrin 0.5 ml.l-1 water, Bacillus thuringiensis 2 g. l-1 water, Beauveria bassiana 2 g.l-1 water and Azadirachta indica 1 ml.l-1 water. Parameters observed were the initial death time, lethal time 50 (LT50), daily mortality, total mortality, intensity attack, temperature and humidity. The results showed that the ability of various insecticide products was different in controlling S. asigna larvae. The insecticides cypermethrin, B. thuringiensis, B. bassiana and A. indica were able to control S. asigna pests with total mortality of 87.5%, 80%, 52.5% and 80% respectively.Keywords: insecticide products, cypermethrin, B. thuringiensis, B. bassiana and A. indica